Nose-to-Brain Delivery - Wang, Zian; Xiong, Guojun; Tsang, Wai Chun; Schätzlein, Andreas G; Uchegbu, Ijeoma F (The Journal of pharmacology and experimental therapeutics, 2019)
The global prevalence of neurologic disorders is rising, and yet we are still unable to deliver most drug molecules, in therapeutic quantities, to the brain. The blood brain barrier consists of a tight layer of endothelial cells surrounded by astrocyte foot processes, and these anatomic features constitute a significant barrier to drug transport from the blood to the brain. One way to bypass the blood brain barrier and thus treat diseases of the brain is to use the nasal route of administration and deposit drugs at the olfactory region of the nares, from where they travel to the brain via mechanisms that are still not clearly understood, with travel across nerve fibers and travel via a perivascular pathway both being hypothesized. The nose-to-brain route has been demonstrated repeatedly in preclinical models, with both solution and particulate formulations. The nose-to-brain route has also been demonstrated in human studies with solution and particle formulations. The entry of device manufacturers into the arena will enable the benefits of this delivery route to become translated into approved products. The key factors that determine the efficacy of delivery via this route include the following: delivery to the olfactory area of the nares as opposed to the respiratory region, a longer retention time at the nasal mucosal surface, penetration enhancement of the active through the nasal epithelia, and a reduction in drug metabolism in the nasal cavity. Indications where nose-to-brain products are likely to emerge first include the following: neurodegeneration, post-traumatic stress disorder, pain, and glioblastoma.